2015
DOI: 10.1155/2015/637809
|View full text |Cite
|
Sign up to set email alerts
|

A Variable Depth Search Algorithm for Binary Constraint Satisfaction Problems

Abstract: The constraint satisfaction problem (CSP) is a popular used paradigm to model a wide spectrum of optimization problems in artificial intelligence. This paper presents a fast metaheuristic for solving binary constraint satisfaction problems. The method can be classified as a variable depth search metaheuristic combining a greedy local search using a self-adaptive weighting strategy on the constraint weights. Several metaheuristics have been developed in the past using various penalty weight mechanisms on the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…We also showed that deep Q-learning is marginally better than machine learning (classification) methods in general, but not always as can be seen in the Table (4). Overall, we claim that our method of deep Q-learning (Version 6.5) can play Minesweeper to a high degree of accuracy while still being fast enough to play boards as large as 200 total blocks.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…We also showed that deep Q-learning is marginally better than machine learning (classification) methods in general, but not always as can be seen in the Table (4). Overall, we claim that our method of deep Q-learning (Version 6.5) can play Minesweeper to a high degree of accuracy while still being fast enough to play boards as large as 200 total blocks.…”
Section: Discussionmentioning
confidence: 53%
“…CSP is another prominent way of formulating the Minesweeper game in a mathematical form and several algorithms [22] exist to solve these CSPs. CSPs are the subject of intense research in both AI and operations research since not only it overcomes the problems in single-point strategy, but the regularity in their formulation provides a common basis to analyze and solve problems of many unrelated families [11,4]. MDP is another way of formulating games into state-action-reward form.…”
Section: Related Workmentioning
confidence: 99%
“…Ref. [35], BalancedZ [36], Score 2 SAT [37], CCAnrSim [38], CryptoMiniSAT [39], Sparrow [27], MapleCOMSPS_LRB_VISDIS [39], and previously DLM [13], SAPS [14], PAWS [15], and DDFW [28,40]).…”
Section: Dynamic Local Search and Maxsatmentioning
confidence: 99%
“…The central idea is to reduce the size of local search space relying on a continual relaxation (removing elements from the solution) and re-optimization (re-inserting the removed elements). Finally, the work introduced in [16] introduces a variable depth metaheuristic combing a greedy local search with a self-adaptive weighting strategy on the constraints weights.…”
Section: Introductionmentioning
confidence: 99%